Analisis Tantangan dan Peluang Integrasi Prinsip Blue Accounting dalam Sistem Perpajakan Daerah untuk Optimalisasi Pendapatan Asli Daerah (PAD) Kabupaten Kepulauan Aru - Ester Melania Pasamba (Akubis : Jurnal Akuntansi dan Bisnis, 2025)
Aru Islands Regency has enormous marine resource potential, but its contribution to Local Own-Source Revenue (PAD) remains low due to a financial management system that does not optimally accommodate the economic value of marine ecosystems. This phenomenon is exacerbated by a lack of data transparency and the absence of accounting instruments which is capable of comprehensively measuring marine assets. Blue accounting has emerged as a potential solution to integrate the ecological and economic value of marine resources into the regional taxation system. However, its implementation faces various challenges, such as unsupportive regulations, limited human resource capacity, and resistance from business actors. This study aims to analyze the challenges and opportunities of integrating blue accounting into the taxation system to increase PAD in the Aru Islands Regency. The research method uses a qualitative approach with data collection techniques through in-depth interviews with stakeholders, field observations, and policy document studies. The results show that the application of blue accounting can open up significant opportunities, such as the potential for additional PAD from the fisheries sector and blue carbon taxes. However, the main challenges include fragmentation of marine resource data, lack of inter-agency coordination, and low public awareness of the benefits of sustainable economy. Strategic solutions are needed, including the formulation of special regional regulations, strengthening human resource capacity through training, and utilizing digital technology for marine resource monitoring.